Sordacan en 1994 - Parizeau, Robert (Assurances, 1995)
The recession we have just experienced has shaken the very foundations of most sectors of activity, notably the financial sector. Stimulated by economic growth in the U.S., the recovery taking hold in Europe and the weakness of the Canadian dollar, exports have become the engine for economic expansion in Canada. Consumers nevertheless have remained wary and employment growth, although comforting, has fallen short of expectations.